Polycystic Ovary Syndrome May Be an Autoimmune Disorder - Hifsa Mobeen; Nadeem Afzal; Muhammad Kashif (Scientifica)
Polycystic ovarian syndrome (PCOS) is the most prevalent endocrine disorder affecting females. It is a common cause of menstrual irregularities and infertility during reproductive age. Genetic and hormonal factors play crucial role in the pathogenesis of PCOS. Low level of progesterone in PCOS causes overstimulation of immune system that produces more estrogen which leads to various autoantibodies. Different autoantibodies have been documented in PCOS, for example, anti-nuclear (ANA), anti-thyroid, anti-spermatic, anti-SM, anti-histone, anti-carbonic anhydrase, anti-ovarian, and anti-islet cell antibodies. There is an association between PCOS and autoimmune diseases such as ANA and anti-TPO that have been documented in systemic lupus erythematosus and Hashimoto thyroiditis, respectively, and it is suspected that there are autoantibodies that might affect the long term clinical management of these patients. Therefore fluctuating levels of autoantibodies in different PCOS patients give us the way to open new chapter for future research on molecular level. This may lead to discovery of better treatment options for PCOS in near future.